Un informe de lectura de Jaume Riera i Sans sobre un procés medieval inquisitorial de l'any 1405, conservat a l'Arxiu Diocesà de Barcelona. - VILA, PEP (Scripta)
In the spring of 2014, I asked my friend Jaume Riera i Sans, archivist and historian, if he could take a critical look at an inquisitorial process from the Diocesan Archive of Barcelona. Here we offer his detailed reading report, full of digressions and wise considerations. Given the significance of the text, I was convinced that, sooner than later, this text would end up being transcribed, accompanied by a good study. He didn't have the time to do it.